Flow Patterns and Particle Residence Times in the Oral Cavity during Inhaled Drug Delivery - Brenda Vara Almirall; Kiao Inthavong; Kimberley Bradshaw; Narinder Singh; Aaron Johnson; Pippa Storey; Hana Salati (Pharmaceuticals, 2022)
Pulmonary drug delivery aims to deliver particles deep into the lungs, bypassing the mouth–throat airway geometry. However, micron particles under high flow rates are susceptible to inertial impaction on anatomical sites that serve as a defense system to filter and prevent foreign particles from entering the lungs. The aim of this study was to understand particle aerodynamics and its possible deposition in the mouth–throat airway that inhibits pulmonary drug delivery. In this study, we present an analysis of the aerodynamics of inhaled particles inside a patient-specific mouth–throat model generated from MRI scans. Computational Fluid Dynamics with a Discrete Phase Model for tracking particles was used to characterize the airflow patterns for a constant inhalation flow rate of 30 L/min. Monodisperse particles with diameters of 7 <semantics>μ</semantics>m to 26 <semantics>μ</semantics>m were introduced to the domain within a 3 cm-diameter sphere in front of the oral cavity. The main outcomes of this study showed that the time taken for particle deposition to occur was 0.5 s; a narrow stream of particles (medially and superiorly) were transported by the flow field; larger particles > 20 <semantics>μ</semantics>m deposited onto the oropharnyx, while smaller particles < 12 <semantics>μ</semantics>m were more disperse throughout the oral cavity and navigated the curved geometry and laryngeal jet to escape through the tracheal outlet. It was concluded that at a flow rate of 30 L/min the particle diameters depositing on the larynx and trachea in this specific patient model are likely to be in the range of 7 <semantics>μ</semantics>m to 16 <semantics>μ</semantics>m. Particles larger than 16 <semantics>μ</semantics>m primarily deposited on the oropharynx.